A calalogue mi benthic marine algae of Almería (S.L. of Spain) - Conde, Francisco; Soto Moreno, Juan (Botanica Complutensis, 1989)
Soio. J. & CONOE. F. 1989. A catalogue on benthic marine algae of Almeria <5. E. of Spain). Bo!. (omplutensis 15: 61–83 (i n Spanish). The number of taxa of algae in Almería coasts are 325. 12 of them, are new records for Iberian Peninsula coasts: Audouinella subpinnata, Lithophyl/um incrus/ans f. depressa, L. incrus¡uns f.flabe//ata. Polystrata compactes, Nithophy/lumflabellatum, Lophocladia la//em andiL Polysiphonia atra, Feldmannia padinaé Glifordia o rata, Streb/onema sti/ophoraé; Ochlochaete histrix y Chaetosiphon mo/iniformis. Symphyocarpus strangulans is a new record for Spanish Mediterranean coast.